PERAN PEMERINTAH DESA DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT DI DESA TIRTANADI KECAMATAN LABUHAN HAJI KABUPATEN LOMBOK TIMUR: The Role of Village Government in Improving the Community Economy in Tirtanadi Village, Labuhan Haji District, East Lombok - M. Naufal Nadzir Al Mardho (Yayasan Al-Amin Qalbu, 2025)
Villages are the spearhead in improving the community's economy. Villages have direct contact with community activities and production, especially household economics. The aim of this research is to determine the role of the village government in improving the community economy in Tirtanadi Village, Labuhan Haji District, East Lombok Regency. This type of research is survey research with a qualitative approach. Data collection is through observation or directly seeing the conditions that occur and interviews as well as documentation or viewing documents related to the research. The research results show that the Tirtanadi Village government has a strategic role in improving the community's economy through village development planning, developing BUMDes, empowering MSMEs, developing economic infrastructure, and optimizing local potential. These programs have had a positive impact on improving community welfare, although they are still faced with various obstacles, such as limited human resources and market access.